Faecal calprotectin testing for identifying patients with organic gastrointestinal disease: systematic review and meta‐analysis. Issue 10 (3rd November 2019) - An, Yoon‐Kyo; Prince, David; Gardiner, Fergus; Neeman, Teresa; Linedale, Ecushla C; Andrews, Jane M; Connor, Susan; Begun, Jakob
Abstract: Objectives: To assess the clinical effectiveness of faecal calprotectin (FC) testing for distinguishing between organic gastrointestinal diseases (organic GID), such as inflammatory bowel disease (IBD), and functional gastrointestinal disorders (functional GIDs). Study design: Studies that assessed the accuracy of FC testing for differentiating between IBD or organic GID and functional GIDs were reviewed. Articles published in English during January 1998 – June 2018 that compared diagnostic FC testing in primary care and outpatient hospital settings with a reference test and employed the standard enzyme‐linked immunosorbent FC assay method with a cut‐off of 50 or 100 μg/g faeces were included. Study quality was assessed with QUADAS‐2, an evidence‐based quality assessment tool for diagnostic accuracy studies. Data sources: MEDLINE and EMBASE; reference lists of screened articles. Data synthesis: Eighteen relevant studies were identified. For distinguishing patients with organic GID (including IBD) from those with functional GIDs (16 studies), the estimated sensitivity of FC testing was 81% (95% CI, 74–86%), the specificity 81% (95% CI, 71–88%); area under the curve (AUC) was 0.87. For distinguishing IBD from functional GIDs (ten studies), sensitivity was 88% (95% CI, 80–93%), specificity 72% (95% CI, 59–82%), and AUC 0.89. Assuming a population prevalence of organic GID of 1%, the positive predictive value was 4.2%, the negative predictive value 100%. The difference in sensitivity and specificity between FC testing cut‐offs of 50 μg/g and 100 μg/g faeces was not statistically significant ( P = 0.77). Conclusions: FC testing is clinically useful for distinguishing organic GID (including IBD) from functional GIDs, and its incorporation into clinical practice for evaluating patients with lower gastrointestinal symptoms could lead to fewer patients with functional GIDs undergoing colonoscopy, reducing costs for both patients and the health system. PROSPERO registration: CRD4201810507.